2009
DOI: 10.1128/aem.00580-09
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of [NiFe] Hydrogenase Genes in Metagenomic DNA: Cloning and Heterologous Expression in Thiocapsa roseopersicina

Abstract: Using a metagenomics approach, we have cloned a piece of environmental DNA from the Sargasso Sea that encodes an [NiFe] hydrogenase showing 60% identity to the large subunit and 64% to the small subunit of a Thiocapsa roseopersicina O 2 -tolerant [NiFe] hydrogenase. The DNA sequence of the hydrogenase identified by the metagenomic approach was subsequently found to be 99% identical to the hyaA and hyaB genes of an Alteromonas macleodii hydrogenase, indicating that it belongs to the Alteromonas clade. We were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 58 publications
(59 reference statements)
1
40
0
Order By: Relevance
“…SDS-PAGE was performed as described by Sambrook & Russell (2001). Gels were either stained with Coomassie using the SimplyBlue SafeStain reagent (Invitrogen) or transferred to nitrocellulose and Western blotting was performed using polyclonal rabbit antibodies specific for T. roseopersicina HynL and HynS as the primary antibodies (Sambrook & Russell, 2001;Maró ti et al, 2009 To heterologously express the AltDE [NiFe] hydrogenase in E. coli, we sought to clone the HynSL gene cluster in an expression vector, pTrc-NSI, which contains an IPTG/ lactose-inducible promoter P Trc . The entire 13 kb operon including hynSL and the 11 surrounding genes was amplified by PCR from AltDE genomic DNA in four consecutive and overlapping pieces (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SDS-PAGE was performed as described by Sambrook & Russell (2001). Gels were either stained with Coomassie using the SimplyBlue SafeStain reagent (Invitrogen) or transferred to nitrocellulose and Western blotting was performed using polyclonal rabbit antibodies specific for T. roseopersicina HynL and HynS as the primary antibodies (Sambrook & Russell, 2001;Maró ti et al, 2009 To heterologously express the AltDE [NiFe] hydrogenase in E. coli, we sought to clone the HynSL gene cluster in an expression vector, pTrc-NSI, which contains an IPTG/ lactose-inducible promoter P Trc . The entire 13 kb operon including hynSL and the 11 surrounding genes was amplified by PCR from AltDE genomic DNA in four consecutive and overlapping pieces (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These experiments involved either the transfer of a hydrogenase gene cluster including the entire set of accessory genes (Friedrich et al, 1984;Yagi et al, 1986;Báscones et al, 2000;Lenz et al, 2005) or the transfer of the structural genes and a small subset of the accessory genes with maturation relying upon the accessory proteins of the heterologous host (Rousset et al, 1998;Maró ti et al, 2009). Despite the successful transfer of hydrogenases between several species, there has been limited success in heterologously expressing active [NiFe] hydrogenases in E. coli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The putative [NiFe] hydrogenase HynSL from AltDE displayed 60% identity to the large subunit and 64% to the small subunit of the stable [NiFe] hydrogenase (HynSL) from the purple sulfur bacterium Thiocapsa roseopersicina (12,20,30,54). In a previous study, we identified an Alteromonas [NiFe] hydrogenase from the Sargasso Sea, which is 99% identical to HynSL in AltDE (30).…”
mentioning
confidence: 99%
“…In a previous study, we identified an Alteromonas [NiFe] hydrogenase from the Sargasso Sea, which is 99% identical to HynSL in AltDE (30). The expression of its genes cloned from the Sargasso Sea in the foreign host T. roseopersicina generated an active hydrogenase capable of producing H 2 (30).…”
mentioning
confidence: 99%